Pengenalan Kegiatan Keluarga Untuk Anak Berkebutuhan Khusus (Autis) Menggunakan Media Pembelajaran Berbasis Kinect - Fauzi, Joko Arif Nur, Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Special needs children with autism are children who have developmental disorders and have dificulty in social and communication skill. In the family, a child with autism need to be introduced to learning about family activities. The learning method of children with autism is different from normal children. The learning method have principle to be easly accepted, memorable and enjoyable for the autism kid. One of the methods is to use a game that can attract and increase interest in learning of autistic children. This research aims to create a game that can be used to introduces family activities. this game is based on kinect which make it more interctive and attractive that also helping the autism kids to learn. This research was conducted in SLB Rumah Pintar Salatiga with reference to the curriculum issued by the government and the SLB. this research see students' ability to recognize and remember an activity or an object,because based on interviews with the teachers, every students has different abilities, so the teachers need to repeat the lesson. The main software to create this game are Unity3D, Kinect SDK, Audacity, Adobe Photoshop and Mixamo. The testing of this research is performed by demonstrating the game in front of the students with supervised by the teacher. Based on the questionnaire result, its can be stated that the game is interesting, interactive and the game material according to the curriculum taught in SLB Rumah Pintar Salatiga.